A Novel Compound Targeting Protease Receptor 1 Activators for the Treatment of Glioblastoma - Shavit-Stein, Efrat; Sheinberg, Ehud; Golderman, Valery; Sharabi, Shirley; Wohl, Anton; Gofrit, Shany Guly; Zivli, Zion; Shelestovich, Natalia; Last, David; Guez, David; Daniels, Dianne; Gera, Orna; et al. (Frontiers in Neurology, 2018)
Data from human biopsies, in-vitro and in-vivo models, strongly supports the role of thrombin and its protease-activated receptor (PAR1) in the pathology and progression of glioblastoma (GBM), a high-grade glial tumor. Activation of PAR1 by thrombin stimulates vasogenic edema, tumor adhesion and tumor growth. We here present a novel six amino acid chloromethyl-ketone compound (SIXAC) which specifically inhibits PAR1 proteolytic activation and counteracts the over-activation of PAR1 by tumor generated thrombin. SIXAC effects were demonstrated in-vitro utilizing 3 cell-lines, including the highly malignant CNS-1 cell-line which was also used as a model for GBM in-vivo. The in-vitro effects of SIXAC on proliferation rate, invasion and thrombin activity were measured by XTT, wound healing, colony formation and fluorescent assays respectively. The effect of SIXAC on GBM in-vivo was assessed by measuring tumor and edema size as quantified by MRI imaging, by survival follow-up and brain histopathology. SIXAC was found in-vitro to inhibit thrombin-activity generated by CNS-1 cells (IC50 = 5X10-11M) and significantly decrease proliferation rate (p˂0.03) invasion (p=0.02) and colony formation (p=0.03) of these cells. In the CNS-1 GBM rat animal model SIXAC was found to reduce edema volume ratio (8.8±1.9 vs. 4.9±1, p˂0.04) and increase median survival (16 vs. 18.5 days, p˂0.02 by Log rank Mental-Cox test). These results strengthen the important role of thrombin/PAR1 pathway in glioblastoma progression and suggest SIXAC as a novel therapeutic tool for this fatal disease.